2020
DOI: 10.2217/3dp-2020-0017
|View full text |Cite
|
Sign up to set email alerts
|

3D-Printed Valves to Assist Noninvasive Ventilation Procedures During the Covid-19 Pandemic: A Case Study

Abstract: Aim: To produce valves to be used with full-face snorkeling masks for noninvasive ventilation (NIV) procedure during the coronavirus disease 2019 (COVID-19) pandemic. Materials & methods: ISINNOVA’s Charlotte valves for full-face snorkeling masks used for NIV procedures were redesigned, produced by selective laser sintering additive manufacturing, and submitted to air leakage tests. Results: The final model assembly did not present air leakage during the NIV procedure on human models, minimizing risks of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…The approval process is more critical in manufacturing; thus, the easiest and safest way to meet the demand for medical devices could be the following: industries that received approval for medical devices from the regulatory authority should consider outsourcing parts (components) of the production process from companies in other sectors. However, in partnership with research centers and universities, innovative makers, hobbyists (Armani 2020 ), and several other companies worldwide have been developing alternative PPE kits and medical equipment parts through accelerated production (Longhitano 2020 ; Longhitano and Silva 2021b ; Longhitano et al 2021b ) and at a low cost; for instance, F1 Mercedes, in partnership with engineers and clinicians at University College London, developed a continuous positive airway pressure (CPAP) device that is being successfully tested on COVID-19 patients undergoing treatment before invasive mechanical ventilation (Mahase 2020 ). Nevertheless, many of these measures can void the various warranty and technical assistance contracts and potentially become judicial actions in the future; however, the best way to deal with this situation remains to be defined.…”
Section: Discussionmentioning
confidence: 99%
“…The approval process is more critical in manufacturing; thus, the easiest and safest way to meet the demand for medical devices could be the following: industries that received approval for medical devices from the regulatory authority should consider outsourcing parts (components) of the production process from companies in other sectors. However, in partnership with research centers and universities, innovative makers, hobbyists (Armani 2020 ), and several other companies worldwide have been developing alternative PPE kits and medical equipment parts through accelerated production (Longhitano 2020 ; Longhitano and Silva 2021b ; Longhitano et al 2021b ) and at a low cost; for instance, F1 Mercedes, in partnership with engineers and clinicians at University College London, developed a continuous positive airway pressure (CPAP) device that is being successfully tested on COVID-19 patients undergoing treatment before invasive mechanical ventilation (Mahase 2020 ). Nevertheless, many of these measures can void the various warranty and technical assistance contracts and potentially become judicial actions in the future; however, the best way to deal with this situation remains to be defined.…”
Section: Discussionmentioning
confidence: 99%
“…Copyright@ Suprateek Kundu be 3D printed and made the CAD files available for public with all the necessary printing parameters listed [21]. Longhitano, et al [22]. Provided novel ways to convert full-face snorkeling masks in conjugation with 3D printed valves to be used for NIV procedures.…”
Section: American Journal Of Biomedical Science and Researchmentioning
confidence: 99%
“…Evaluation studies on these prototypes have shown that the masks were airtight, and the valves successfully served the purpose of NIV procedures [22].…”
Section: American Journal Of Biomedical Science and Researchmentioning
confidence: 99%
“…The new model presented no air leakage when coupled to Decathlon's Surface Snorkeling Mask Easybreath R and is currently being used for noninvasive ventilation in COVID-19 patients in various Brazilian Hospitals [15]. More information regarding the valve production, optimization and tests can be found in one of our previously published papers [16].…”
Section: Fighting the Covid-19 Pandemic In Brazilmentioning
confidence: 99%